Conversion of sub-megasized DNA to desired structures using a novel Bacillus subtilis genome vector - Kaneko, Shinya (Oxford University Press, 2003)
A novel genome vector using the 4215 kb Bacillus subtilis genome provides for precise target cloning and processing of the cloned DNA to the desired structure. Each process highly dependent on homologous recombination in the host B.subtilis is distinguished from the other cloning systems. A 120 kb mouse jumonji (jmj) genomic gene was processed in the genome vector to give a series of truncated sub-megasized DNA. One of these truncated segments containing the first intron was copied in a plasmid by a recombinational transfer method developed for B.subtilis. DNA manipulation previously considered difficult is argued with respect to DNA size and accuracy.